Energy requirements, energetic partition and methane emission from growing Holstein, Gyr and F1 Holstein-Gyr dairy heifers - Moreira, Tainá Silvestre (2016)
In Brazil, country with the fifth largest world production of milk, diets formulations are also carried out on the basis of nutritional requirements established in other countries, especially those from predominantly temperate climate. Research validation nutritional systems have evidenced application incompatibility of systems generated in temperate conditions at tropical conditions. Thus, the aim of this study was to determinate energy requirements, energetic partition and methane (CH4) enteric emission from growing Holstein, Gyr and F1 Holstein-Gyr dairy heifers in tropical conditions. The trial was conducted at The Multi-use Livestock Complex of Bioefficiency and Sustainability at Embrapa Dairy Cattle, Coronel Pacheco - MG, Brazil. Were evaluated 36 heifers, 12 Holstein, 12 Gyr and 12 Holstein-Gyr in 3 distinct experiments. In the first one, the 36 heifers were distributed in 12 latin squares, in a 3x3 factorial arrangement which was 3 nutritional plans and 3 genotypes. The nutritional plans were (1) 1.0x maintenance; (2) 1.5x maintenance and (3) 2.0x maintenance and the heifers were fed a diet consisting of 85.0% of corn silage and 15.0% of concentrate on a dry matter (DM) basis. Enteric CH4 emission was evaluated by SF6 tracer technique. Dry matter intake (DMI) and nutrients presented interaction among genotype and nutritional plan. Gyr heifers demonstrated higher crude protein (CP) digestibility (76.55%), F1 Holstein-Gyr intermediary value (75.14%) and Holstein animals presented the lowest value (74.59%). Daily CH4 production (g/d) was influenced by nutritional plan and differed as well between genotypes whereas Gyr heifers compared to the others had lesser CH4 emissions. Heifers fed at lower nutritional plan presented highest (85.5%) CH4 emissions by average daily gain (g/ kg of ADG) when compared to heifers fed at the higher nutritional plan. We found annual emissions of 45.84 kg of CH4. The second experiment has as objective measure the heat production (HP) and the enteric CH4 emission from dairy heifers using face mask (FM) method. The same animals, treatments and diets that were used in the first study were used in this second and third one. The HP expressed in Mcal by metabolic body weight (Mcal/BW0.75) was affect by genotype and Gyr heifers presented lower HP (163.2) when compared to Holstein (201.0) while F1 Holstein-Gyr heifers did not differ (181.3). Observed interaction among genotype and nutritional plan to CH4 emission in (g/d) and grams per kilo of metabolic body weight (g/kg of BW0.75). When expressed in dry matter ingested was not found genotype or nutritional plans effects to CH4 production. In the third study, our objective was to determine energy requirements, energetic partition and enteric CH4 emission using the \"gold standard\" methodology as calorimetric respirometry. Each heifers spent one 24 hours period in an open-circuit respirometric chamber (RC) to measurements. The CH4 emission was influenced by genotype and nutritional plan. Holstein and F1 Holstein-Gyr heifers demonstrated 73.4% superior emissions when compared to Gyr heifers. The net energy requirements for maintenance (NEm/kcal BW0.75) was 103.9 for Holstein heifers, 79.86 for Gyr heifers and 103.8 for F1 Holstein-Gyr heifers. The metabolizable energy requirements for maintenance (MEm/kcal BW0.75) was 132.6 for Holstein heifers, 116.0 for Gyr heifers and 138.2 for F1 Holstein-Gyr heifers. Were not found differences among Holstein and F1 heifers on NEm and MEm, so was formulated a combined equation for both, where the net and metabolizable energy requirements for maintenance were 105.2 and 135.0 kcal/BW0.75, respectively. We concluded that our results about nutritional requirements had similarity with available literature from respirometric chambers. These generated data from dairy cattle will be used for a future data base vising the establishment of feed patterns for representative dairy cattle genotypes in national herd composition. Also, the enteric methane emission data obtained in this study will be used in the greenhouse gases national inventory.